Distribution of spawning and sex ratio in Greenland halibut. - Morgan, J.M.; Garabana-Barro, Dolores; Saborido-Rey, Francisco (2012)
This paper examines spawning area and time and sex ratio by depth from data collected from the commercial fisheries of Canada and Spain and by research vessel surveys conducted by Canada and the EU. The data from commercial fisheries indicate that the proportion female increases with depth. This is particularly evident for depths greater than 600 m. However, the interpretation of the change in sex ratio with depth is complicated by issues of gear selectivity. Spawning fish were found in all areas and in all months. There tended to be a higher proportion of females in spawning condition in the northern areas. Canadian data indicate that spawning is in the summer and autumn while data from Spain seem to indicate more year round spawning. The ability to determine peak spawning time and area is hampered by the lack of sampling throughout the year in all areas.